Spray-dried cyclophosphamide-loaded polyhydroxyalkanoate microparticles: design and characterization - Sergei Lipaikin; Aleksei Dorokhin; Galina Ryltseva; Andrey Oberenko; Evgeniy Kiselev; Alexander Shabanov; Tatiana Volova; Ekaterina Shishatskaya (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Cyclophosphamide (CP) is a widely used antitumor and immunosuppressive drug, but it is highly cytotoxic and has carcinogenic and teratogenic potential. To reduce adverse effects of CP therapy and the frequency of its administration, the microencapsulation of CP into biodegradable polymeric matrices can be performed. However, according to the literature, only a few polymers were found suitable to encapsulate CP and achieve its' sustained release. Experimental approach: In this research, spray-dried cyclophosphamide-loaded poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) microparticles were prepared and characterized in terms of their average hydrodynamic diameter, polydispersity index, surface morphology, zeta potential, encapsulation efficiency, drug loading, thermal properties and cytotoxicity against 3T3 cells. Key results: The obtained CP-loaded microparticles had a regular spherical shape, uniform size distribution with an average diameter of 4.21±0.04 μm and zeta potential of -34.2±0.2 mV. The encapsulation of cyclophosphamide into the PHBV matrix led to a decrease in melting and degradation temperatures and an increase in diameter, glass transition and cold crystallization temperatures compared to blank microparticles. Moreover, microencapsulation of cyclophosphamide lowered its cytotoxicity compared to the pure drug: the number of dead cells in the culture decreased by 28 %, while their metabolic activity increased by 20 %. The cumulative in vitro drug release studies showed a gradual release of CP up to 18 days, so the obtained microparticle formulation can be used as a sustained-release cyclophosphamide delivery system. Conclusion: In this research, a novel cyclophosphamide-loaded platform based on PHBV microparticles was established and characterized. Overall, this study offers promising prospects for cancer therapy in the future.